Short-range structure and photoluminescent properties of the CaTiO3:Pr,La phosphor - Ribeiro, Guilherme K. [UNESP]; Vicente, Fabio S. [UNESP]; Bernardi, Maria Inês B.; Mesquita, Alexandre [UNESP] (Elsevier, 2016)
Pr3+-doped CaTiO3perovskite is a promising phosphor compound with the possibility of use in several technological applications. In this paper, we report the substitution of Ca2+ions with La3+ions in order to promote Ca vacancies to further enhance photoluminescence (PL). CaTiO3:Pr,La samples were prepared by the polymeric precursor method and their short- and long-range structure and photoluminescent properties were investigated in this paper. PL measurements show a narrow emission centered at 612 nm typical of the1D2–3H4transition of Pr3+ions. As the La content increases, the intensity of this peak is increased. This enhancement of PL curves for CaTiO3:Pr,La samples is associated with disorder in the CaTiO3lattice caused by the La incorporation. This disorder as a function of the La content is shown by both X-ray absorption near edge structure (XANES) spectra at the Ti K-edge and Raman spectroscopy measurements. CaTiO3:Pr,La samples do not present PL with long term afterglow.
Keywords: Ca vacancies; Calcium titanate; CaTiO3; Lanthanum; Photoluminescence; Praseodymium; Raman; Red phosphor; Short term afterglow; XANES